Optimal Reproductive Strategy in Yellow-Bellied Marmots: Unveiling the Consequences of Age at First Reproduction on Survival and Lifetime Reproductive Success - Chabot, Carol-Ann (Université d'Ottawa / University of Ottawa, 2023)
When to reproduce for the first time is a key question in evolutionary ecology. Indeed, age at first reproduction has clear impacts on population dynamics and fitness. Breeding early in life may impair survival due to a resource allocation trade-off between survival, growth, and reproduction. Postponing reproduction, however, reduces reproductive opportunities and increases the chances of dying before reproducing. Here, I investigate the consequences of age at first reproduction on both survival and lifetime reproductive success by using long-term monitoring data of a population of yellow-bellied marmots (Marmota flaviventer) at the Rocky Mountain Biological Laboratory (Colorado, USA). Mixed models were employed to analyze the relationships between age at first reproduction in females and their lifetime reproductive success, as well as three survival components: longevity, the number of years after first reproduction, and annual survival probability. The results showed that postponing reproduction until 2 years of age increased longevity, but delaying it beyond 2 years did not yield additional survival benefits. Females reproducing for the first time after 3 years exhibited high rates of actuarial senescence. Furthermore, delaying first reproduction beyond 3 years old did not lead to a compensatory increase in lifetime reproductive success that would offset the reduction in survival associated with postponing first reproduction. These results suggest that the optimal age at first reproduction, in terms of survival and reproductive success, is 2 years. The reproductive strategy might be governed by body condition or environmental factors. These findings shed light on the trade-offs between early reproduction and survival, as well as reproductive success, illustrating the complexity of reproductive strategies in relation to individual fitness.
Keywords: age at first reproduction; trade-off; yellow-bellied marmot; survival